Robust Surface Coating for a Fast, Facile Fluorine-18 Labeling of Iron Oxide Nanoparticle for PET/MR Dual-modality Imaging() - Sun, Ziyan (Nanoscale, 2016)
Grafting a robust organic shell around inorganic nanoparticles can optimize their colloidal features to dramatically improve their physicochemical properties. Here, we developed a polymer coating procedure for providing colloidal stability to the nanoparticles and, more importantly, for applying a fast, facile fluorine-18 labeling of iron oxide nanoparticle (IONP) for positron emission tomography (PET)/magnetic resonance (MR) dual-modality imaging. The structure of the amphiphilic polymer is based on a backbone of polyacrylic acid, conjugated with multiple oleylamines to form a comb-like branched structure. The dense polymer shell provides high colloidal stability to the IONPs against the harsh conditions such as high temperature, low pH value, and high ion strength. By incorporating the 1,4,7-triazacyclononane (NOTA) chelator to the comb-like amphiphilic polymer for the chelation of aluminum fluoride ions, we applied a one-step radiolabeling approach for a fast, facile radiofluorination of magnetic nanoparticles. The new strategy can significantly reduce the procedure time and radiation exposure. The PET/MR dual modality imaging was successfully achieved in living subjects by using (18)F labeled magnetic nanoparticles.